Evaluation of Empirical and Preemptive Therapy Approaches of Invasive Mold Infections in Patients with Hematologic Malignancy - Ozdemir, Yusuf Emre; Surme, Serkan; Bayramlar, Osman Faruk; Ozdemir, Meryem Sahin; Elverdi, Tugrul; Salihoglu, Ayse; Balkan, Ilker Inanc; Mete, Bilgul; Eskazan, Ahmet Emre; Ar, Muhlis Cem; et al. (Cerrahpaşa Medical Journal, 2023)
Objective: We aimed to evaluate the diagnostic and therapeutic approaches of invasive mold infections (IMIs) in febrile neutropenic patients. Methods: This retrospective and single-center study includes patients with hematologic malignancy and IMIs. Predictors for 30-day and 1-year mortality were determined. Results: A total of 87 patients were recorded. Of whom, 48 (55.2%) were male and the mean age was 44.56±15.83. Twenty patients were in the empirical therapy group and 67 were in the preempitive group. Galactomannan positivity rate was found 24.1% (n=21). The causative agents were detected in 16 patients. In the initial treatment, liposomal amphotericin-B (n=53), voriconazole (n=27), caspofungin (n=5), and posaconazole (n=1) were used. The 30-day mortality rate was 26.4%, while the 1-year mortality rate was 44.8%. The 30-day (45.0% vs. 20.9%, p=0.03) and 1-year (65% vs. 38.8%, p=0.04) mortality rates were significantly higher in empirical treatment group than in preemptive treatment group. In multivariate analysis, presence of blasts in peripheral blood (p=0.04, 95%CI=1.01-9.38, OR=3.07) was determined as an independent risk factor for 30-day mortality. No independent risk factor was found for 1-year mortality. Conclusion: As a result, despite the early initiation of empirical treatment, preemptive therapy approach was as effective as empirical approach in the management of IMIs. Therefore, invasive and non-invasive diagnostic methods should be used more frequently to decrease overtreatment. In conclusion, current interdisciplinary approaches are crucial for evidence-based early diagnosis in immunocompromised patients with hematologic malignancies.